EDUCATIONAL VALUES OF THE MAIN CHARACTERS IN “THE IMPORTANCE OF BEING EARNEST” DRAMA BY OSCAR WILDE - Lenny Solo (Department of English Education, Universitas Panca Sakti Bekasi, 2020)
Educational values play important role in the human lives. These values are found in many literary works. Play is a literary works portrayed many educational values. This study aims to analyze the important of educational values portrayed and to investigate how the educational values integrated in The Importance of Being earnest play by Oscar Wilde in people education. The qualitative approach is applied this study. It studied the data in written or oral word descriptively. The primary data is taken from the script of The Importance of Being earnest play. It also uses references on literary books and some relevant materials as its secondary data to support and complete each other. This study found that The Importance of Being earnest play portrayed the following educational values: responsible, curiosity, creative, hard work, honest, and discipline. Besides, Oscar Wilde also ask the reader to become earnest in everyone in our life.